Platinum‐Based Nanowires as Active Catalysts toward Oxygen Reduction Reaction: In Situ Observation of Surface‐Diffusion‐Assisted, Solid‐State Oriented Attachment. Issue 46 (20th October 2017) - Ma, Yanling; Gao, Wenpei; Shan, Hao; Chen, Wenlong; Shang, Wen; Tao, Peng; Song, Chengyi; Addiego, Chris; Deng, Tao; Pan, Xiaoqing; Wu, Jianbo
Abstract: Facile fabrication of advanced catalysts toward oxygen reduction reaction with improving activity and stability is significant for proton‐exchange membrane fuel cells. Based on a generic solid‐state reaction, this study reports a modified hydrogen‐assisted, gas‐phase synthesis for facile, scalable production of surfactant‐free, thin, platinum‐based nanowire‐network electrocatalysts. The free‐standing platinum and platinum–nickel alloy nanowires show improvements of up to 5.1 times and 10.9 times for mass activity with a minimum 2.6% loss after an accelerated durability test for 10k cycles; 8.5 times and 13.8 times for specific activity, respectively, compared to commercial Pt/C catalyst. In addition, combined with a wet impregnation method, different substrate‐materials‐supported platinum‐based nanowires are obtained, which paves the way to practical application as a next‐generation supported catalyst to replace Pt/C. The growth stages and formation mechanism are investigated by an in situ transmission electron microscopy study. It reveals that the free‐standing platinum nanowires form in the solid state via metal‐surface‐diffusion‐assisted oriented attachment of individual nanoparticles, and the interaction with gas molecules plays a critical role, which may represent a gas‐molecular‐adsorbate‐modified growth in catalyst preparation. Abstract : Free‐standing platinum and platinum–nickel alloy nanowires are synthesized by a modified facile hydrogen‐assisted gas‐phase method. In situ transmission electron microscopy observation reveals that the formation of nanowires is attributed to surface‐diffusion‐assisted, solid‐state oriented attachment. The Pt and Pt1.3 Ni‐alloy nanowires exhibit promising catalytic activity and excellent stability compared with commercial Pt/C toward oxygen reduction reaction.